Effect of heterologous expression of FT gene from Medicago truncatula in growth and flowering behavior of olive plants. - Guerrero-Ruiz, Consolación María; Cerezo Medina, Sergio; Feito, Isabel; Rodríguez-Pérez, Lucía; Samach, Alon; Mercado-Carmona, José Ángel; Pliego-Alfaro, Fernando; Palomo-Ríos, Elena (Frontiers Media, 2024)
Olive (Olea europaea L. subsp. europaea) is one of the most important crops of the Mediterranean Basin and temperate areas worldwide. Obtaining new olive varieties adapted to climatic changing conditions and to modern agricultural practices, as well as other traits such as biotic and abiotic stress resistance and increased oil quality, is currently required; however, the long juvenile phase, as in most woody plants, is the bottleneck in olive breeding programs. Overexpression of genes encoding the ‘ﬂorigen’ Flowering Locus T (FT), can cause the loss of the juvenile phase in many perennials including olives. In this investigation, further characterization of three transgenic olive lines containing an FT encoding gene from Medicago truncatula, MtFTa1, under the 35S CaMV promoter, was carried out. While all three lines ﬂowered under in vitro conditions, one of the lines stopped ﬂowering after acclimatisation. In soil, all three lines exhibited a modiﬁed plant architecture; e.g., a continuous branching behaviour and a dwarﬁng growth habit. Gene expression and hormone content in shoot tips, containing the meristems from which this phenotype emerged, were examined. Higher levels of OeTFL1, a gene encoding the ﬂowering repressor TERMINAL FLOWER 1, correlated with lack of ﬂowering. The branching phenotype correlated with higher content of salicylic acid, indole-3-acetic acid and isopentenyl adenosine, and lower content of abscisic acid. The results obtained conﬁrm that heterologous expression of MtFTa1 in olive induced continuous ﬂowering independently of environmental factors, but also modiﬁed plant architecture. These phenotypical changes could be related to the altered hormonal content in transgenic plants.
Keywords: Olivos - Genética; Genética vegetal; Olivos - Floración; Olea europaea L. subsp. europaea; FT gene; TFL gene; Flowering; Branching phenotype; Hormonal content